2022
DOI: 10.1126/scitranslmed.abq1945
|View full text |Cite
|
Sign up to set email alerts
|

Dual spike and nucleocapsid mRNA vaccination confer protection against SARS-CoV-2 Omicron and Delta variants in preclinical models

Abstract: Emergence of SARS-CoV-2 variants of concern (VOCs), including the highly transmissible Omicron and Delta strains, has posed constant challenges to the current COVID-19 vaccines that principally target the viral spike protein (S). Here, we report a nucleoside-modified messenger RNA (mRNA) vaccine that expresses the more conserved viral nucleoprotein (mRNA-N) and show that mRNA-N vaccination alone can induce modest control of SARS-CoV-2. Critically, combining mRNA-N with the clinically proven S-expressing mRNA v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
105
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 67 publications
19
105
1
Order By: Relevance
“…Our murine model provided additional insights into specific features of T cell immunity within various anatomical sites. In addition to humoral responses, cellular immunity contributes to protection against COVID-19 and recent evidence suggests that viral-vector and mRNA vaccines elicit long-lasting S-specific or nucleoprotein-specific CD4 + and CD8 + T cell responses, with broad cross-reactivity against VOCs 29 , 30 . While T RM cells are induced by high concentration mRNA vaccines 31 ; we report that lower concentrations of unmodified mono- or bivalent mRNA vaccines induced lung parenchymal tissue resident T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our murine model provided additional insights into specific features of T cell immunity within various anatomical sites. In addition to humoral responses, cellular immunity contributes to protection against COVID-19 and recent evidence suggests that viral-vector and mRNA vaccines elicit long-lasting S-specific or nucleoprotein-specific CD4 + and CD8 + T cell responses, with broad cross-reactivity against VOCs 29 , 30 . While T RM cells are induced by high concentration mRNA vaccines 31 ; we report that lower concentrations of unmodified mono- or bivalent mRNA vaccines induced lung parenchymal tissue resident T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging pre-clinical data suggest a potential role for vaccine-elicited nucleocapsid responses in controlling virus replication in the lung 29 . Though the limited sequence evolution in nucleocapsid compared to spike could make nucleocapsid an attractive target, the shorter durability of circulating antibodies against nucleocapsid compared to spike following infection necessitates the study of the comparative durability of vaccine-elicited nucleocapsid versus spike antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, on-going analyses of licensed SARS-CoV-2 vaccine efficacy has shown that vaccine-induced immunity wanes over time, resulting in breakthrough infections 2022 . In addition, intranasal administration of mRNA vaccines to mice did not confer protection against SARS-CoV-2 challenge 23 . As a result, there is a growing need to develop a second generation of SARS-CoV-2 vaccines that can be administered through intranasal routes to induce protective mucosal immunity 24,25 .…”
Section: Introductionmentioning
confidence: 94%